2021
DOI: 10.3390/app112411595
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Traffic Sign Retro-Reflectivity Degradation Using Deep Neural Networks

Abstract: Traffic signs are essential for the safe and efficient movement of vehicles through the transportation network. Poor sign visibility can lead to accidents. One of the key properties used to measure the visibility of a traffic sign is retro-reflection, which indicates how much light a traffic sign reflects back to the driver. The retro-reflection of the traffic sign degrades over time until it reaches a point where the traffic sign has to be changed or repaired. Several studies have explored the idea of modelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In a 2021 study, Alkhulaifi et al [9] used regression models and neural networks based on deep learning models. The neural network with one-hot encoding achieved the best results with an R 2 value of 0.976, while polynomial regression models achieved an R 2 of 0.759.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2021 study, Alkhulaifi et al [9] used regression models and neural networks based on deep learning models. The neural network with one-hot encoding achieved the best results with an R 2 value of 0.976, while polynomial regression models achieved an R 2 of 0.759.…”
Section: Systematic Literature Reviewmentioning
confidence: 99%
“…Previous studies have suggested prediction models based on two features (sheeting type and color). Most of these studies focused on age as the only predictor for retroreflectivity performance, with Alkhulaifi [9], who considered color and observation angle, in The coefficient of retroreflection can be measured using retroreflectometers, while spectrophotometers are used for measuring colors. In the field, measurements can be recorded using either handheld or mobile equipment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ML and DL have found various applications in diverse fields such as face recognition and tracking [2], visual tracking [3,4], vision and language navigation [5][6][7], and image and video editing [8][9][10]. In recent years, application of such soft computing methodologies has received widespread applications for various civil and transportation engineering-related problems, including road safety [11][12][13][14], mode choice modeling [15], energy demand modeling for electric vehicles [16][17][18], and traffic sign detection and recognition [19,20]. Similarly, applications of these predictive modeling approaches are reshaping the field of pavement evaluation and management.…”
Section: Introductionmentioning
confidence: 99%
“…However, the aforementioned standards do not give designers many opportunities to influence these requirements: while the criteria for motorized roads (class M) include the "navigational task difficulty" criterion (albeit with limited impact on the lighting class which generally pertains to driving rather than walking), the criteria for pedestrian and low-speed areas (class P, which is applicable in such situations) are not applicable in this specific case [19]. The same happens with the coexistence of public lighting and groves in urban environments [20][21][22], and also with different kinds of traffic signals [23,24]. Both are systematically ignored by rulemaking bodies and, rather frequently, by designers.…”
mentioning
confidence: 99%